PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Raniyah, Raniyah; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of modernization of taxation administration system to the personal taxpayer compliance level Kantor Pelayanan Pajak Pratama Surabaya Gubeng. This research has been done by using quantitative research method. This research uses primary data which has been obtained by issuing questionnaires and accidental sampling technique which is directed to the personal taxpayers who are in the scope of population at Kantor Pelayanan Pajak Pratama Surabaya Gubeng. The result of the research shows that organization strategy gives positive influence to the personal taxpayer compliance level in KPP Pratama Gubeng Surabaya. This is supported by the convenience of the taxpayers in accessing taxation requirements which is begun from register themselves to the socialization which is facilitated by using online-based technology. Organization structure, organization and organization culture does not give any influence to the personal taxpayer compliance level because the attitude and behavior of the tax apparaturs is less concerned by the personal taxpayer.Keywords: Modernization of Taxation Administration System, Personal Taxpayer Compliance Level, Personal Taxpayer.